Animals in world history - Cowie, Helen (Helen Louise), author. Link
1 online resource (xi, 234 pages)
Keywords: "This volume provides a concise synthesis of human-animal relations over time, charting shifting attitudes towards animals from domestication to the present day. It asks how non-human species have shaped human history, and how humans have reconfigured the animal world. Humans have had a long and close relationship with animals. They have hunted them, consumed them as food and fashion, exploited them as energy sources, utilised them in warfare, exhibited them in zoos and menageries, and studied them for science. In the process, they have radically changed the way in which many animals live, subjecting them to captivity, altering their diets, constraining their movements and, through selective breeding, reshaping their bodies. The book explores the use of animals for sustenance, labour, companionship and display and traces the rise of the animal rights movement. It also assesses how humans have impacted the overall biodiversity of the planet, driving some species of animals to extinction and permitting others to colonise new continents. With case studies on animal astronauts, celebrity kakapos, globetrotting pandas and cocaine hippos, Animals in World History offers a lively and accessible introduction to human-animal relations for students and instructors of animal studies, environmental history, and social and cultural history"--